Determination of Potassium Levels in Bananas Using an Optical Sensor with a Flat and Concave Mirror Plane - Mohammad Budiyanto; Muhamad Arif Mahdiannur; Wahyu Budi Sabtiawan; Tutut Nurita; Elok Sudibyo (Postgraduate, University of Mataram, 2021)
Potassium is a nutrient that plays a role in maintaining the function of the muscles and nerves that control the heart and is needed for body stability. The potassium content in the body can be obtained from foods such as bananas. The development of instruments and methods that are developed to obtain a more accurate measurement of potassium concentration requires an instrument that has high linearity and sensitivity. The instrument is in the form of an optical sensor system equipped with the use of optical fibers to guide the waveform to maintain its intensity stability. In this study, an experimental method was conducted with a sample of a standard solution with potassium as the solute and pure water as the solvent. Then continue to measurements on samples of banana milk and green banana fruit extracts. The results of the analysis of the measurement data using an optical sensor with a concave mirror reflection plane obtained a sensitivity of 0.36 mV/ppm and a linearity of 82.56%. In the plane of the flat mirror reflection, obtained an optical sensor with a plane mirror reflection plane shows a sensitivity of 0.12 mV/ppm and a linearity of 97.6%. The highest and most accurate linearity value is found in the plane mirror plane results. The next stage is the result of the maximum output voltage read on the optical detector through an optical sensor with a sample of extracts of milk banana and green banana. The results of data analysis on the linear equation with the highest linearity obtained the potassium content in milk bananas of 391.54 ppm and the green banana extract solution obtained 307.91 ppm, so it can be concluded that the potassium content in milk bananas is higher than green bananas with a linearity of more than 97%.